Game programming algorithms and techniques : a platform-agnostic approach - Madhav, Sanjay, ....- (Upper Saddle River : Addison Wesley, 2014)
Game Programming Algorithms and Techniques is a detailed overview of many of the important algorithms and techniques used in video game programming today. Designed for programmers who are familiar with object-oriented programming and basic data structures, this book focuses on practical concepts that see actual use in the game industry.
Indludes index.
Keywords: Computer games -- Programming